An Experimental Study on Digital Media Integrated Movie Clips for EFL Students’ Vocabulary Mastery - Pradana, Muhammad Priyo Gading; Kalisa, Pasca (Universitas Muhammadiyah Barru, 2026)
This study focuses on whether or not EFL students' vocabulary mastery might be improved by using digital learning tools, specifically the Cake mobile application in conjunction with real-world movie clips. A quasi-experimental methodology was used, drawing on other studies that highlight the potential of mobile assisted language acquisition and audiovisual input for vocabulary development. 64 eleventh-grade students from SMA Teuku Umar Semarang participated in the study. They were split into two groups: an experimental group that received training via the Cake app and movie clips, and a control group that received instruction via traditional techniques. 50-item multiple-choice pre-tests and post-tests were used to gauge vocabulary proficiency. An independent-samples t-test was used after normality and homogeneity testing in the data analysis. The results showed that while both groups improved, there was no significant difference between the experimental and control groups (sig. = 0.217 > 0.05). These findings suggest that better vocabulary increases are not always the result of integrating digital media and movie clips. The results may have been impacted by elements including insufficient contextual scaffolding, limited repeated exposure, and variations in learner preparedness for mobile assisted learning. In terms of pedagogy, the study recommends that in order to optimize their efficacy, digital media should be integrated into thoughtfully crafted educational frameworks that offer clear direction, contextualized practice, and prolonged exposure to target vocabulary.